2012
DOI: 10.1016/j.virol.2012.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species regulate the replication of porcine circovirus type 2 via NF-κB pathway

Abstract: Intracellular redox state has been suggested to have various effects on the replication of different viruses within host cells. The aim of the present study was to investigate the influence of reactive oxygen species (ROS) on replication of porcine circovirus type 2 (PCV2), in PK15 cells. Following PCV2 infection there was a time-dependent increase in ROS. Antioxidant N-acetyl-l-cysteine treatment of cells resulted in lower ROS levels and lower PCV2 replication. In contrast, treatment by buthionine sulfoximine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 37 publications
4
54
0
2
Order By: Relevance
“…In particular, a previously published study reported that FHC is induced downstream of NF-kB and inhibits TNFainduced apoptosis by suppressing ROS (Pham et al, 2004). As activation of the NF-kB signalling pathway and production of ROS were reportedly detected in PCV2-infected PK15 cells (Wei et al, 2008;Chen et al, 2012), the interaction between ORF4 and host FHC may be responsible for inhibition of apoptosis by PCV2 during its early infection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, a previously published study reported that FHC is induced downstream of NF-kB and inhibits TNFainduced apoptosis by suppressing ROS (Pham et al, 2004). As activation of the NF-kB signalling pathway and production of ROS were reportedly detected in PCV2-infected PK15 cells (Wei et al, 2008;Chen et al, 2012), the interaction between ORF4 and host FHC may be responsible for inhibition of apoptosis by PCV2 during its early infection.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, a time-dependent increase in ROS during PCV2 infection has been reported (Chen et al, 2012), and this progression was shown to alter NF-kB activity (Chen et al, 2012). Activation of the NF-kB pathway promotes the expression of pro-inflammatory molecules, such as TNFa, E-selectin, P-selectin, ICAM-1 and VCAM-1 (Berberat et al, 2003), and is thus a crucial component of the cellular defence against PCV2 infection .…”
Section: Orf4 Suppresses Reactive Oxygen Species (Ros) Accumulation Imentioning
confidence: 99%
“…APS can reduce oxidative stress occurs [20], which imply that APS is likely to resist the replication of PCV2 by its antioxidant activity. Interaction between PCV2 infection and intracellular redox status, which is associated with the alteration in NF-B pathway induced by oxidative stress [21]. We supposed that the effect of APS on PCV2 replication in vitro related to oxidative stress and NF-B pathway, and finally we clarified APS worked by inhibiting oxidative stress and blocking NF-B pathway.…”
Section: Introductionmentioning
confidence: 93%
“…But whether oxidative stress increase in PCV2 replication could be eliminated by APS? Since compound BSO can cause irreversible inhibition of GSH biosynthesis and decrease the capacity to detoxify ROS, BSO increased intracellular oxidative stress state [21]. To address this question, PCV2, BSO + PCV2, APS + PCV2, BSO + PCV2 + APS groups were set up, respectively.…”
Section: Effect Of Aps On Pcv2 Replication Related To Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation